Export development Of artisanal products - Merriam, Caroline Ramsay; Merriam, Caroline Ramsay; Benjamin, Malcolm; Crafts Center; United Nations Conference on Trade and Development (Geneva International Trade Centre, 1998)
Handicrafts. study reviewing various steps and approaches for presenting, promoting and placing artisanal products in international markets - reviews overall markets situation, explores effective means of technical assistance and trade promotion support, and identifies major areas where they are needed, provides advice to entrepreneurs and producers, discusses intellectual property rights with regard to the sector, also focuses on marketing artisanal products through trade fairs and the internet; includes selected list of relevant organizations, trade fairs and publications.
Introduction -- Chapter 1 Artisanal Products: the past and the present, products and markets -- Chapter 2 Trade promotion: technical assistance and support to the craft industries -- Chapter 3 Principal areas for technical cooperation in trade promotion -- Chapter 4 Export development: advice to entrepreneurs and business persons -- Chapter 5 Intellectual property rights and crafts -- Chapter 6 Marketing crafts through trade fairs -- Chapter 7 Marketing crafts through the internet --
This paper was prepared jointly by the International Trade Centre UNCTAD/WTO and the Craft Center
Bibliography: P. [94]
Keywords: International Trade; INTERNATIONAL TRADE; EXPORTS; HANDCARTS; TECHNICAL ASSISTANCE; TECHNICAL COOPERATION; TRADE PROMOTION